Early Holocene sea level in the Canadian Beaufort Sea constrained by radiocarbon dates from a deep borehole in the Mackenzie Trough, Arctic Canada. (24th July 2018) - O'Regan, Matt; Coxall, Helen; Hill, Philip; Hilton, Robert; Muschitiello, Francesco; Swärd, Henrik
Abstract : Deglacial and Holocene relative sea level (RSL) in the Canadian Beaufort Sea was influenced by the timing and extent of glacial ice in the Mackenzie River corridor and adjacent coastal plains. Considerable evidence indicates extensive ice cover in this region of northwestern Canada during the Late Wisconsinan. However, no absolute ages exist to constrain maximum RSL lowering before the late Holocene (4.2–0 ka). In 1984, the Geological Survey of Canada drilled an 81.5‐m‐deep borehole in the western Mackenzie Trough at 45 m water depth (MTW01). The lower 52.5 m of the borehole was interpreted as a deltaic progradational sequence deposited during a period of rising sea level. The upper 29 m was described as foraminifer‐bearing marine sediments deposited after transgression of the site, when RSL rose above −74 m. Here, we present radiocarbon measurements from MTW01, acquired from benthic foraminifera, mollusc fragments and particulate organic carbon in the >63 μm fraction (POC>63 μm ) in an attempt to constrain the chronology of sediments within this borehole and date the timing of transgression. The deepest carbonate macrofossil was acquired from 8 m above the transgressive surface (equivalent to 21 m b.s.l.), where mollusc fragments returned a date of 9400 +180–260 cal. a BP (2σ). This provides the oldest constraint on Holocene sea‐level lowering in the region, and implies that transgression at this site occurred prior to the early Holocene. Ages obtained from the lower 52.5 m of the borehole are limited to POC>63 μm samples. These indicate that progradational sediments were deposited rapidly after 24 820 +390–380 cal. a BP (2σ). Due to the incorporation of older reworked organic matter, the actual age of progradation is likely to be younger, occurring after Late Wisconsinan glacial ice retreated from the coast.